Implementasi Model Inovasi Pembelajaran di SMP Berbasis Pesantren Daarussholah - Siti Munfiatik (AL-AMIYAH: Jurnal Ilmiah Multidisiplin, 2024)
This research aims to describe and analyze learning innovation models, learning innovation implementation models, and obstacles to implementing learning models in Islamic boarding school-based junior high schools. The method used is a qualitative descriptive method. This research was carried out at the Daarussholah Islamic Boarding School in South Sangatta. The research results show that the learning innovation models are as follows: contextual learning (CTL), cooperative learning, problem-based learning, e-learning, inquiry-based learning, and value clarification technique (VCT) learning. However, one is often used, namely, the value clarification technique (VCT) learning innovation model. Meanwhile, the application of the learning innovation model places more emphasis on changing attitudes, behaviours, and good habits. The obstacles to implementing the learning innovation model at the Daarussholah Pesantren-based Middle School in South Sangatta are limited facilities and infrastructure, a lack of openness between students and teachers, student habits that are difficult to direct, and parental intervention in discipline matters. Thus, it is hoped that the results of this research will provide a comprehensive understanding of learning innovation models, their implementation, and the obstacles faced for further development and improvement in efforts to improve the quality of education.